Women in the eighteenth century : constructions of femininity - Jones, Vivien, 1952- (London ; New York : Routledge, 1990)
Complementing the current upsurge in feminist writing on the eighteenth century, and giving students the chance to make their own re-readings of texts, this anthology gathers together a range of material from conduct manuals to medical texts.
Feminisms. from A serious proposal to the ladies, for the advancement of their true and greatest interest / Mary Astell -- from An essay in defence of the female sex -- from The hardships of the English laws in relation to wives -- 'Sophia', from Beauty's triumph, or, The superiority of the fair sex invincibly proved, 1751 ; Part one, Woman not inferior to man, 1739 -- from Appeal to the men of Great Britain in behalf of the women / Mary Hays -- from A letter to the women of England, on the injustice of mental subordination / 'Anne Frances Randall' [Mary Robinson].
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Women -- Great Britain -- History -- Sources; Women -- Great Britain -- Literary collections; English literature -- Women authors; Women -- England -- Social conditions; Écrits de femmes anglais; Femmes -- Angleterre -- Conditions sociales; Littérature et société -- Angleterre; Femmes -- Grande-Bretagne -- Histoire -- Sources; Femmes -- Grande-Bretagne -- Anthologies; SOCIAL SCIENCE -- Women's Studies; English literature -- Women authors; Women; Great Britain; Frau; Literatur; Quelle; Großbritannien; Anthologie; Frau; Vrouwen; Sociale situatie; Mulher E Feminismo; Historia Da Europa; Femmes et littérature -- Grande-Bretagne -- 18e siècle.; Femmes -- Grande-Bretagne -- 18e siècle -- Sources; Femmes -- Conditions sociales -- 18e siècle.; Femmes -- Dans la littérature.; Englisch; Society -- Role of women; Literature; History; Literary collections; Sources; Literature; Littérature.